EFEKTIFITAS HYPNOBREASFEEDING TERHADAP KELANCARAN PEMBERIAN ASI PADA IBU POST PARTUM DI PUSKESMAS BIARO - Wahyuni Wahyuni; Yori Sulistia (Maternal Child Health Care, 2022)
Early breastfeeding initiation (IMD) is one of the actions that can influence the success of breastfeeding and exclusive breastfeeding. Many problems of breastfeeding are caused by the inability of production and expenditure of breast milk, so mothers are forced to provide additional food at early ages (0-6 months), including in the work area of Biaro Health Center which still has problems with achieving exclusive breastfeeding. This study aims to determine the effectiveness of hypnobreastfeeding on breastfeeding at Biaro Health Center in Agam Regency in 2018. This type of research is Quasy Experimental Design with the Two Group Post Test approach. This research was conducted in July - December 2018 in the Biaro Health Center with a population of all postpartum mothers, as many as 23 people. Sampling by purposive sampling with a sample of 20 people. Data collection used observation sheets, data analysis included univariate analysis and bivariate analysis using parametric statistics, namely independent t-test. The results showed that the average breastfeeding measured by the frequency of BAK in 24 hours in the intervention group was 7.7 and in the control group was 5.1 times. There is a difference in the average breastfeeding measured by BAK infants between the intervention group and the control group with an average difference of 2.6 times and p-value = 0.011. It was concluded that the administration of hypnobreasfeeding interventions was effective in increasing breastfeeding. For this reason, it is expected that all parties, especially health officials, can develop non-pharmacological techniques to increase breastfeeding, one of which is by providing hypnobreastfeeding interventions that have proven effective in improving breastfeeding. Keywords         : Hypnobreastfeeding, breastfeeding